2022
DOI: 10.1149/1945-7111/ac4aae
|View full text |Cite
|
Sign up to set email alerts
|

Modified Sawhorse Waveform for the Voltammetric Detection of Oxytocin

Abstract: Carbon fiber microelectrodes (CFMEs) have been used to detect neurotransmitters and other biomolecules using fast-scan cyclic voltammetry (FSCV) for the past few decades. This technique measures neurotransmitters such as dopamine and, more recently, physiologically relevant neuropeptides. Oxytocin, a pleiotropic peptide hormone, is physiologically important for adaptation, development, reproduction, and social behavior. This neuropeptide functions as a stress-coping molecule, an anti-inflammatory agent, and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…This velocity, computerized control, and signal averaging enable repetitive trials and increase the signal-to-noise-ratio (SNR). 15 Recent work has introduced continuous SWV (cSWV) which collects current continuously during the SWV waveform to extract multiple voltammograms from a single scan. 16 This shows promise for conformation switching biosensors by rapidly assessing frequency dependence.…”
Section: Current Statusmentioning
confidence: 99%
See 2 more Smart Citations
“…This velocity, computerized control, and signal averaging enable repetitive trials and increase the signal-to-noise-ratio (SNR). 15 Recent work has introduced continuous SWV (cSWV) which collects current continuously during the SWV waveform to extract multiple voltammograms from a single scan. 16 This shows promise for conformation switching biosensors by rapidly assessing frequency dependence.…”
Section: Current Statusmentioning
confidence: 99%
“… 49 Other studies have used this waveform to differentiate dopamine and other monoamines from other tyrosine-containing neuropeptides such as oxytocin based on the varied oxidation potentials of the molecules. 15 When applied with MSW (multiple scan rates) on CFMEs, FSCV also provides information on real-time oxytocin effects on rat brain slices, exposing its impact on physiology and social behavior. 15 , 50 The Jackson (serotonin) N-shaped waveform was also shown to be optimal for the detection of serotonin with FSCV.…”
Section: Current Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…These investigations demonstrated the potential of innovative methods for detecting oxytocin in a rapid, sub-second timeframe. This could have important ramifications for measuring oxytocin levels in living organisms and advancing our knowledge of the physiological functions of oxytocin [181].…”
Section: Application In Oxytocin Detectionmentioning
confidence: 99%
“…Using CFMEs and FSCV has several advantages over other techniques as they have fast electron transfer kinetics [ 21 ], high spatiotemporal resolution [ 22 ], biocompatibility [ 23 ] and are minimally invasive. CFMEs have also been used for the detection of other molecules in addition to neurotransmitters such as metals [ 24 , 25 , 26 ] and more complex molecules such as amino acids [ 27 , 28 ] and neuropeptides [ 29 ]. Through waveform modification, it has been shown that the detection of several molecules can be optimized with FSCV.…”
Section: Introductionmentioning
confidence: 99%